An 'omics approach towards CHO cell engineering. Issue 5 (4th February 2013) - Datta, Payel; Linhardt, Robert J.; Sharfstein, Susan T.
Abstract Chinese hamster ovarian cells (CHO) cells have been extensively utilized for industrial production of biopharmaceutical products, such as monoclonal antibodies, human growth hormones, cytokines, and blood‐products. Recent advances in recombinant DNA technology have resulted in the bioengineering of CHO cells that have robust gene amplification systems and can also be adapted to grow in suspension cultures. In parallel, recent advances in techniques and tools for decoding the CHO cell genome, transcriptome, proteome, and glycome have led to new areas of study for better understanding the metabolic pathways in CHO cells with the long‐term goal of developing new biologics. This review paper discusses the recent advances in bioengineering strategies in CHO cell lines and the impact of the knowledge gained by CHO cell genomics, transcriptomics, and glycomics on the future of CHO‐cell engineering. Biotechnol. Bioeng. 2013; 110: 1255–1271. © 2013 Wiley Periodicals, Inc.